Computer-Assisted Sperm Analysis of Freezable and Nonfreezable Mithun (Bos frontalis) Semen. (18th August 2014) - Perumal, P.; Srivastava, S. K.; Ghosh, S. K.; Baruah, K. K.
Abstract : The present study was undertaken to assess the motility and velocity parameters of sperm of freezable and nonfreezable ejaculates by computer-assisted sperm analyser (CASA) such as Hamilton-Thorne Semen Analyser IVOS 11 in mithun semen. Fifty ejaculates (twenty-five ejaculates each for freezable and nonfreezable semen ejaculates) were collected from ten matured mithun bulls. CASA parameters, motility parameters such as forward progressive motility (FPM) (%), nonprogressive motility (NPM) (%), total motility (TM) (%), and static sperms (SM) (%); velocity parameters such as curvilinear velocity (VCL) ( μ m/sec), straight line velocity (VSL) ( μ m/sec), average path velocity (VAP) ( μ m/sec), linearity (LIN) (%), straightness (STR) (%), wobble (WOB) (%), amplitude of lateral head displacement (ALH) ( μ m), and beat/cross-frequency (BCF) (Hz) were measured by CASA analyser. The result revealed that these parameters varied significantly (P < 0.05 ) between the freezable and nonfreezable ejaculates and freezable ejaculates have significantly (P < 0.05 ) higher value than nonfreezable ejaculates. It was concluded that most of the CASA parameters were significantly lower in nonfreezable ejaculates than in freezable ejaculates in mithun and confirmed that the CASA was effective for a quick and objective analysis of motility and velocity parameters in mithun semen.